A history of Russia - Riasanovsky, Nicholas Valentine (Oxford University Press, 1963)
Riasanovsky's History of Russia has defined the market and set a standard for accurate, balanced interpretation, and attention to political, social, and cultural history and international relations. Featuring a new co-author, Mark Steinberg, this seventh edition includes more information on the politics and economics of post-Socialism and on post-Soviet society and culture.